Strategi Peningkatan Daya Saing Dengan Meningkatkan Kualitas Pengelolaan Keuangan Dan Modal Pada UMKM POPKID.ID - Santi Rimadias; Erric Wijaya; M. Bugo Vandori (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
This community service program focuses on strategies to increase the competitiveness of MSMEs in POPKID.ID Children's Clothing by improving the quality of financial and capital management. POPKID.ID is an MSME engaged in the convection of children's clothing aged 1-13 years which has been established since 2020. One of the main problems faced by POPKID.ID is limited working capital which hinders business growth and development. The purpose of this community service activity is to provide training and assistance related to financial and capital management strategies for POPKID.ID. The method used is through training and mentoring. As a result, financial projections show an upward trend if financial and capital management is improved. Suggested strategies include optimizing funding sources and increasing financial literacy.